Mekanisme Pertahanan Diri Chris Dalam Film Into The Wild - Neisya Neisya; Karindrati Karindrati (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2022)
This research aims to describe the conflicts happened to the main character, Chris, in the movie Into the Wild. This conflict then results the self defense mechanism done by Chris to cope with the problem. The method used was qualitative with descriptive approach. To collect the data, firstly the researchers watched the movie several times and then read the transcript of the movie to get the comprehensive understanding. Meanwhile, in analyzing the data, some notes related to the research problem taken before were reduced and finally concluded. The research results are Chris faced both the internal conflict and external conflict in the movie. The internal conflict is related to the psychological turmoil while the external conflict tends to physical and social conflict. The entire conflict faced by Chris finally led him to do self-defense mechanism, namely repression and displacement. As the conclusion, all the conflicts encountered by Chris both internal and external, resulted the repression and displacement as his self-defense mechanism to deal with the conflicts.